(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The quality of service in hotel industry is an important factor of successful business. The existing trend of complete quality management in hotel industry ensures the achievement of competitive advantage of hotel companies and is therefore the subject of contemporary research into service quality in hotel industry. The concept and the conceptual model of service quality is indispensable if we wish to understand the genesis of service quality and potential gaps in quality.